2009
DOI: 10.1515/bc.2009.081
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between kinin and angiotensin II receptors in mouse abdominal aorta

Abstract: Bradykinin (BK) is a vasorelaxant, algesic and inflammatory agent. Angiotensin II (AngII) is known to control vascular tone and promote growth, inflammation and artherogenesis. There is evidence for cross talking between BK and AngII receptors. Therefore, the effect of lack of kinin receptors was assessed in mice with genetic disruption of B(1) or B(2) and both receptors. Responsiveness of abdominal aortic rings to BK and AngII as well as the receptor gene expression of both peptides were analysed. Although no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Furthermore, other important genes are affected by genetic deletion of either kinin receptor. For instance, genetic disruption of B 1 R or B 2 R and both receptors decreased ACE and ANG II AT 1 R function and expression in mice abdominal aorta, indicating that kinin receptors regulate AT 1 receptors and ACE [76], [77]. Moreover, B 2 R knockout mice have increased ANG II AT 2 R mRNA and protein expression that contributes to elevation of NO as compensatory protective mechanism in thrombosis [78].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other important genes are affected by genetic deletion of either kinin receptor. For instance, genetic disruption of B 1 R or B 2 R and both receptors decreased ACE and ANG II AT 1 R function and expression in mice abdominal aorta, indicating that kinin receptors regulate AT 1 receptors and ACE [76], [77]. Moreover, B 2 R knockout mice have increased ANG II AT 2 R mRNA and protein expression that contributes to elevation of NO as compensatory protective mechanism in thrombosis [78].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore several transgenic animals have been created, such as mice deficient in the kinin B 1 R [21,28], in the kinin B 2 R [5,9,10,12] and also in both kinin B 1 R and B 2 R [8], as well as mice overexpressing the B 1 R [17,19] or the B 2 R [34]. It has been shown that the lack of kinin receptors may affect the reactivity of the vascular smooth muscle preparations or cause changes in the expression level of some receptors of kallikrein kinin system (KKS) and renin angiotensin system (RAS) in the same tissue [26].…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of kinin receptors gene causes downregulation of ANG II receptors [31]. Therefore, a decrease in vascular AT1R expression may be involved in the anti-hypertrophic effects of the B1R antagonist.…”
Section: Discussionmentioning
confidence: 99%